Simultaneous tartrazine-tetracycline removal and hydrogen production in the hybrid electrocoagulation-photocatalytic process using g-C3N4/TiNTAs - Husein, Saddam; Rustamadji, Ryan Rafi; Pratiwi, Reno; Dewi, Eniya Listiani; Slamet (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
This study aimed to investigate the removal of tartrazine dye & tetracycline antibiotic and hydrogen (H2) production simultaneously through the hybrid electrocoagulation-photocatalytic process using g-C3N4/TiO2 nanotube arrays (TiNTAs) nanocomposite. The g-C3N4/TiNTAs was used as the photocatalyst. The melamine as the precursor of g-C3N4 was varied to obtain the optimal loading on the removal of tartrazine dye & tetracycline antibiotic and hydrogen (H2) production simultaneously. The integrated acrylic photoreactor was equipped with two 250-W mercury lamps. The nanotubular morphology of TiNTAs and nanostructure features of g-C3N4/TiNTAs were examined using FESEM/EDX and HR-TEM/SAED. The XRD patterns indicated the composition of TiNTAs, confirming the presence of anatase and rutile crystalline phases. UV-Vis DRS also showed a redshift in the composite absorbance and a reduced bandgap with g-C3N4 introduction. The results showed that when tartrazine and tetracycline were treated simultaneously, tartrazine was more dominantly degraded compared to tetracycline. In mixed pollutant system condition, the H2 production increased by 17.0% and 41.1% compared to single pollutant system of tartrazine and tetracycline, respectively. The photocatalyst used in the hybrid process was the g-C3N4/TiNTAs (3 g) which provide the optimum H2 production.